Comparative study of apically extruded debris using one manual and two rotary instrumentation techniques for endodontic retreatment - Alper Kustarci; Demet Altunbas; Kerem Engin Akpinar (Elsevier, 2012)
Background/purpose: The aim of the this study was to compare the amount of debris apically extruded during endodontic retreatment using two rotary nickel-titanium (NiTi) instruments (K3 and R-Endo) and Hedström files. Materials and methods: Forty-five extracted human mandibular premolar teeth were used in this study. Root canals of the teeth were filled before being randomly assigned to three groups. In group 1, gutta-percha was removed with K3 (SybronEndo, West Collins, CA, USA) rotary NiTi instruments. In group 2, gutta-percha was removed with R-Endo (Micro-Mega, Besançon, France) rotary NiTi instruments. In group 3, gutta-percha was removed using Hedström files (Dentsply Maillefer, Ballaigues, Switzerland). Debris extruded from the apical foramen was collected into Eppendorf tubes. The liquid inside the tubes was dried, and the debris in each group was weighed and compared. Data were statistically analyzed using one-way analysis of variance, and Kruskal-Wallis test and Mann-Whitney U test. Results: Although all retreatment techniques resulted in apical extrusion, groups 1 and 2 produced significantly less apical extrusion than group 3 (P<0.05). No statistically significant difference was found between groups 1 and 2 (P>0.05). Conclusion: All retreatment techniques produced extruded debris during endodontic retreatment; however, both rotary NiTi systems were associated with less apical extrusion than manual instrumentation with Hedström files.